Smurf2‐mediated degradation of EZH2 enhances neuron differentiation and improves functional recovery after ischaemic stroke. Issue 4 (25th March 2013) - Yu, Yung‐Luen; Chou, Ruey‐Hwang; Shyu, Woei‐Cherng; Hsieh, Shu‐Ching; Wu, Chen‐Shiou; Chiang, Shu‐Ya; Chang, Wei‐Jung; Chen, Jia‐Ni; Tseng, Yen‐Ju; Lin, Yu‐Hsuan; Lee, Wei; Yeh, Su‐Peng; et al.
Abstract EZH2 plays an important role in stem cell renewal and maintenance by inducing gene silencing via its histone methyltransferase activity. Previously, we showed that EZH2 downregulation enhances neuron differentiation of human mesenchymal stem cells (hMSCs); however, the underlying mechanisms of EZH2‐regulated neuron differentiation are still unclear. Here, we identify Smurf2 as the E3 ubiquitin ligase responsible for the polyubiquitination and proteasome‐mediated degradation of EZH2, which is required for neuron differentiation. A ChIP‐on‐chip screen combined with gene microarray analysis revealed that PPARγ was the only gene involved in neuron differentiation with significant changes in both its modification and expression status during differentiation. Moreover, knocking down PPARγ prevented cells from undergoing efficient neuron differentiation. In animal model, rats implanted with intracerebral EZH2‐knocked‐down hMSCs or hMSCs plus treatment with PPARγ agonist (rosiglitazone) showed better improvement than those without EZH2 knockdown or rosiglitazone treatment after a stroke. Together, our results support Smurf2 as a regulator of EZH2 turnover to facilitate PPARγ expression, which is specifically required for neuron differentiation, providing a molecular mechanism for clinical applications in the neurodegenerative diseases.